Influence of Community-Based Interventions on Routine Immunization Uptake among Children Under Five Years in Ntungamo District-Uganda - Topher, Byamukama; Margaret, Keraka; Eliphas, Gitonga (Texila International Journal of Public Health, 2022)
Evidence of the effectiveness of community-based interventions in improving immunization coverage in populations of low coverage is limited. Vaccine-preventable diseases is a major public health challenge in low-income countries where Uganda lies, and immunization is the only reliable strategy for child survival. The study's objective was to assess the influence of a community-based intervention on the uptake of immunization services to recommend strategies to health stakeholders to improve immunization coverage. A quasi-experimental study was conducted in three phases. Structured and key informant interviews were used as data collection tools. Phase one provided baseline data before the intervention, the second phase was a community-based intervention, and the third phase was post-intervention evaluation. There was no significant difference on the uptake of BCG, POLIO-0, POLIO-1, POLIO-2, DPTHeP-Hib1, DPTHeP-Hib2, PCV1 and PCV2 immunizations between the intervention and control group post-intervention (P= 1.00, α =0.5). The level of knowledge on immunization was 68.8% and 29.6% in the intervention and control groups, respectively. The difference between the two was statistically significant (P=0.00 = α= 0.5). There was a significant association between the level of knowledge of the caregivers on immunization and the uptake of immunization services (P=0.00, α=0.5). There was also a statistically significant difference in immunization coverage between the intervention and control groups (97.5%) and (75.1%) for the intervention and control groups, respectively. The difference was statistically associated with the community-based intervention (P =0.00, α=0.5). Community-based interventions influenced the uptake of routine immunization services.